About St. John's Wort (Hypericum Perforatum L.): Investigation of Morphology, Mechanisms of Action, Activity, Side Effects and Drug Interactions - Şengül, Fatma; Çakır, Melikşah; Öztürk, Beyza; Çakmak, Ayşenur; Vatansev, Hüsamettin (Hayrullah YAZAR, 2021)
Objective: This review provides information about Hypericum perforatum L., known as St. John's Wort. Although many studies have been conducted on H. perforatum and reviews have been written on certain activities, no comprehensive review of St. John's wort plant has been found in the literature. Our review reveals a difference in the comprehensive content of the plant. In this study, many studies about St. John's Wort have been scanned and a detailed review has been made on the plant's morphological properties, chemical composition, therapeutic effects, mechanisms of action, drug interactions and side effects of these compounds.Methods: The studies about St. John's Wort plant between 1992 and 2021 were utilized by using PubMed and Google Scholar databases where international studies in the field of health are published.Results: Humans have benefited from the therapeutic properties of plants from past to present. Observing the therapeutic properties of plants for various diseases has directed scientists to search chemistry of plants. Active pharmaceutical ingredients were achieved with the discovery of biologically active compounds from plants. Hypericum perforatum L. is one of the plants that has been the subject of many studies. However, the use of herbs without separating the active ingredients has also been included in the studies. John's wort plant is an important plant that is frequently used by our people for therapeutic purposes and has also been the subject of many scientific researches. It is perennial herbaceous plant a belonging to the Hypericaceae family. The bright yellow, star-shaped flowers, often clustered in a trio, have five petals and the leafs contain tiny transparent oil glands resembling perforations. The active components of the plant are hypericin and hyperforin. It is generally used internally in the treatment of acute and chronic pain and externally in the treatment of scars and burns.Conclusions: It has been demonstrating that St. John's Wort plant offers therapeutic effect potential for many diseases by using various metabolic pathways in the body, however, it has been shown that its use will be beneficial under the supervision of a doctor by taking into considering the drug interactions and side effect profile.

Amaç: Bu derleme St. John’s wort olarak bilinen Hypericum perforatum L. bitkisi hakkında bilgiler sunmaktadır. H.perforatum hakkında pek çok çalışma yapılmış, belirli aktiviteler üzerine derlemeler yazılmış olmasına rağmen literatürde sarı kantaron bitkisini kapsamlı olarak ele alan derlemeye rastlanmamıştır. Bu çalışmada bitkinin morfolojik özellikleri, kimyasal bileşimi, bu bileşiklerin terapötik etkileri, etki mekanizmaları, ilaç etkileşimleri ve yan etkileri hakkında detaylı bir derleme oluşturulmuştur. Derlememiz bitkiye ait kapsamlı içeriğiyle farklılık ortaya koymayı amaçlamaktadır.Metot: Derleme hazırlanırken sağlık alanında uluslararası çalışmaların yayınlandığı PubMed ve Google Scholar veri tabanları kullanılarak 1992-2021 arasında sarı kantaron hakkında yapılan çalışmalardan faydalanılmıştır.Bulgular: Geçmişten günümüze insanlar bitkilerin tedavi edici özelliklerinden yararlanmıştır. Bitkilerin çeşitli hastalıkları tedavi edici özelliklerinin görülmesi, bilim insanlarını bitkilerin kimyasını araştırmaya yöneltmiştir. Bitkilerdeki biyolojik aktif bileşiklerin ortaya konmasıyla birlikte etken maddeler preklinik ve klinik çalışmalara konu edilmiştir. Bununla birlikte bitkilerin etken maddelerinden ayrışmadan kullanılması da çalışmalarda yer almıştır. Sarı kantaron bitkisi halkımız tarafından terapötik amaçla sıklıkla kullanılan, aynı zamanda pek çok bilimsel araştırmaya konu olmuş, önemli bir bitkidir. Hypericaceae familyasına ait olan bitki parlak sarı, sıklıkla üçlü kümeler şeklinde beş petale sahiptir ve yaprakları, minik saydam yağ bezlerine benzeyen delikler içerir. Aktif major bileşenleri hiperisin ve hiperforindir. Sıklıkla, yara ve yanıkların tedavisinde topikal olarak; depresyon, akut ve kronik ağrı tedavisinde ise oral olarak kullanılmaktadır.Sonuç: Sarı kantaron bitkisinin vücuttaki çeşitli metabolik yolakları kullanarak pek çok hastalık için terapötik etki potansiyeli sunduğu, bununla birlikte kullanımının ilaç etkileşimleri ve yan etki profili göz önüne alınarak doktor kontrolünde yapılmasının fayda sağlayacağı ortaya konulmuştur.
Sarı Kantaron'a Dair (Hypericum Perforatum L.): Morfoloji, Etki Mekanizmaları, Aktivite, Yan Etkileri ve İlaç Etkileşimlerinin İncelenmesi
Keywords: Public Health; Halk Sağlığı; Environmental Health; Çevre Sağlığı